Angina bullosa hemorrhagica: a rare condition? - Adrine Maciel da Rosa; Fernanda Geraldo Pappen; Ana Paula Neutzling Gomes (Revista Sul-Brasileira de Odontologia, 2013)
Angina bullosa hemorrhagica is characterized by oral mucosal blood-filled vesicles or blisters. These lesions, however, are frequently asymptomatic and they are only observed when their content is spilled over the oral cavity. Objective: The aim of this study was to perform a retrospective evaluation of Angina Bullosa Hemorrhagica (ABH) cases diagnosed in patients referred to the Diagnosis Center of Oral Diseases of the Dentistry School of Federal University of Pelotas, over a 4-years period. Material and methods: All the clinical records from this period were reviewed and Angina Bullosa Hemorrhagica could be diagnosed in 47 patients. The following information pertaining to the patient and the lesion were collected from the dental record: gender, age, ABH site, size of the lesion, presence of symptoms, bleeding, likely predisposing factors, treatment and recurrence of the lesion. Results: The results revealed 47 patients with clinical features of ABH, 26 were female and 21 were male, with ages between 42 to 87 years. Thirty-six patients (76.6%) developed the lesion in the palate. Pain was reported by 17 patients (36.2%) and bleeding by 19 patients (40.4%). Seventeen patients (36.2%) reported the occurrence of the lesion following trauma. Conclusion: It is possible to conclude that although ABH has been traditionally described as a rare condition, the data obtained in this study suggest a fairly high occurrence of the disease.